The Use of Ultrasound to Improve Axillary Vein Access and Minimize Complications during Pacemaker Implantation. Issue 5 (23rd March 2016) - ESMAIEL, ABDULLAH; HASSAN, JEREMY; BLENKHORN, FAY; MARDIGYAN, VARTAN
Abstract : Background: The Agency for Healthcare Research and Quality in the United States recommends the use of ultrasound (US) for central venous access to improve patient outcomes. However, in a recent publication, US is still underutilized for axillary vein access during pacemaker implantation. Objective: We sought to describe a technique for US‐guided axillary vein access during pacemaker implantation and to report complication rates and success rate. Methods: Retrospective data collection included success rate and complications on all pacemaker implants by one operator since implementing the systematic use of US at our institution, from November 2012 to January 2015. For the last 59 cases, data were collected prospectively to include time of venous access and number of attempts. Results: A total of 403 consecutive patients were included in the analysis. Two leads were implanted in 255 cases and one lead was implanted in 148 cases. The rate of successful US‐guided access was 99.25%. There were no access‐related complications. The average number of venipuncture attempts was 1.18 per patient. The average time to obtain venous access was 2.24 minutes including the time to apply the sterile US sleeve. Conclusion: The described technique has the potential to improve the success rate of axillary vein access and minimize complications during pacemaker implantation.